The strength law of coir fiber-reinforced soil based on modified Duncan-Chang model - Yang, Hui; Li, Penghui; Yang, E; Jiang, Xueliang; Chen, Jiayu (Frontiers in Earth Science, 2023)
A large diameter triaxial sample of 61.9mm was made by adding coir fiber into red clay. The range of confining pressure was 50kpa to 200kPa; fiber content was 0.1% to 0.4%; and fiber length was 10mm to 40mm. By varying the confining pressure, fiber content and fiber length, the unconsolidated and undrained triaxial tests were used to study the shear strength variation law of coir fiber-reinforced soil. The experimental data were processed to establish a linear model of the segmental elastic modulus, and linear analysis was used to determine the model fitting parameters and to improve the Duncan-Chang model by combining the concept of damage ratio. The modified Duncan-Chang model fits the stress-strain relationship of coir-reinforced soil. The results show a clear dividing line for the effect of fiber length and fiber content on the strength of the samples, which is about 30 mm and 0.3%, respectively. At the same time, the modified model can fit the stress-strain relationship of coir fiber-reinforced soil and reflect the stress-strain curve characteristics of coir fiber-reinforced soil.